The Effect Of Budgetary Participation On Government Apparatus Performance With Organizational Culture As A Moderating Variable (Empirical Study On Maluku Province Organizations - Febbraio Pierre Alfons; Paul Usmany; Christina Sososutiksno (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of budget participation on government apparatus performance with organizational culture as a moderating variable in Regional Apparatus Organizations (OPD) of Maluku Province. Budget participation is seen as an important factor in increasing the effectiveness of the implementation of apparatus duties and responsibilities, while organizational culture plays a role in shaping mindsets, work behaviors, and commitment to achieving organizational goals. This study uses a quantitative approach by distributing questionnaires to apparatus in a number of OPDs in Maluku Province, then the data is processed using moderated regression analysis. The results show that budget participation has a positive and significant effect on government apparatus performance. In addition, organizational culture is proven to moderate the relationship, where a strong organizational culture strengthens the influence of budget participation in improving apparatus performance. These findings indicate that improving apparatus performance requires not only active involvement in the budget preparation process, but also the support of a conducive, adaptive, and performance-oriented organizational culture. This study contributes to local governments in formulating strategies to improve performance through strengthening budget participation and developing organizational culture.